Применение энергосберегающих устройств в интеллектуальных комплексах - Павлусенко, М. Н. (ХНУРЕ, 2012)
The given work is devoted the modem systems economyenergy with saving of comfort level of luminosity. The main task is dymmyrovannye‘s lamps, application of the sensor-based system after the design and calculation in the environment of DIALux.
Keywords: интеллектуальный комплекс; энергосберегающие устройства